Desa Tangguh Penyakit Mulut Dan Kuku (PMK) Berbasis Peternakan Rakyat - Moh. Zali Moh. Zali; Diasyurannita Adeputri Marheni; Selvia Nurlaila; Joko Purdiyan (STIE Malangkucecwara, 2022)
Foot and Mouth Disease (FMD) in Bukek village is an alarming condition considering that Bukek village is a strategic area for the distribution of livestock between regions in Tlanakan district. The need for treatment from this point in the prevention of the spread and treatment of sick livestock. The output of this service is expected to increase the knowledge of breeders, control FMD, and the formation of an independent PMK task force in Bukek village. The methods used in service activities include; cattle breeding counseling, supplementary feeding (UMB), vitamin injection and livestock stimulation and the establishment of a FMD task force. Monitoring and evaluation are carried out to measure the success of activities. As a result of the service activities, the people of Bukek village were very enthusiastic about participating in counseling activities and understanding the pattern of cattle breeding, prevention and treatment of FMD. The provision of UMB and herbal booster FMD is given to farmers as many livestock as they have between 1-2ltr / livestock. The provision of vitamins and vaccination of livestock was carried out with relevant officials covering the ernak population in Bukek village. Vaccination data recording was submitted to the relevant service, assisted by a veterinarian from Madura University. The establishment of the PMK task force in the village was ratified by a decree of the village head for each hamlet there is representation, who has the task and obligation to record and report livestock indicated to be affected by FMD. Babinsa and Bhabinkantibmas also help in sanitary spraying of the pen using disinfectants periodically.